Pengaruh Struktur Modal dan Kualitas Aktiva Produktif terhadap Kinerja Keuangan pada Bank Syariah di Indonesia - Fadila Thalib; Siti Nurhaliza Koniyo (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2025)
This study aims to determine the effect of capital structure on financial performance, productive assets on financial performance, and capital structure and productive assets on financial performance at Bank Syariah Indonesia. The research method used is quantitative using documentary data collection techniques. The data source used in this research is secondary data. The secondary data used is the financial statements of Bank Syariah Indonesia in 2015-2018 which are taken from the official website of the BSI Annual Report. The financial ratios used are debt to Equity Ratio, Earning Asset Quality, and Return On Assets. The data analysis technique used in this study is the classic assumption test, normality test, multicolonierity test, auto correlation test and heterocodasitation test. In this research it is found that (1) partially Debt to Equity (DER) has a negative and significant effect on Return on Assets (ROA) at Islamic Commercial Banks in Indonesia, (2) partially Earning Asset Quality (KAP) has a negative and significant effect on Return on Assets (ROA) at Islamic Commercial Banks inIndonesia, and (3) simultaneously Debt to Equity Ratio (DER) and Earning Asset Quality (KAP) have a joint and significant effect.